Some issues of analysis structural complex systems - Normatov R.N; Aripov M.M; Siddikov I.M (International Journal on Orange Technologies, 2021)
The article deals with the analysis of indicators of structurally complex systems, the structure of which can be displayed as a network graph. An example of bringing a system with a complex structure to a recurrent form is given.